THE EFFECT OF THE DIFFERENT GEAR RESISTANCE EXERCISES ON THE MAXIMUM CONSUMPTION OF OXYGEN (VO2MAX) AND THE strenJth CHARACTERIZED BY SPEED AND TIME OF ACHIEVING (15) KM AGAINST THE CLOCK FOR CYCLISTS - Jassim Mkhilf Al-SHihany, Alaa (International Journal of Psychosocial Rehabilitation, 2020)
This experimental study aims to identify the effect of different resistance exercises by using gears in the maximum consumption of oxygen (Vo2max), the strength characterized by speed, and the time of completing a distance of (15) km against the clock for nascent cyclists. The study included a random sample of (16) nascent cyclists who were participating in the Iraqi league for cycling (2017). The study subjects were randomly divided into study and control groups; each group included eight subjects. The researcher prepared resistance exercises refined by the gears' resistance and the time of achieving determined distances according to the aerobic energy system via continuous training, which was applied for 15 minutes in the final part of the time of the main section of the training session. Such an application was at the rate of two training sessions per training week for (12) training weeks. The researcher concluded that the resistance exercises of different gears improved the maximum Vo₂max, improved the strength characterized by speed for the leg muscles of the cyclists, and improved the time of completing a distance of (15) km against the clock.